2012
DOI: 10.1111/j.2044-8279.2012.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization and school disaffection: Exploring the moderation effect of social support and the mediation effect of depression

Abstract: The results of this study are consistent with the main effect model of social support. They also highlight the importance of teacher support for school adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 150 publications
3
42
0
Order By: Relevance
“…Our finding that girls reported more fear of victimization complies with the previously documented gender difference (Boulton et al ., ). The main effect of peer support complements the understanding of peer support as a feature relevant to various facets of adjustment (Galand & Hospel, ; Prinstein et al ., ). The main effect of classroom victimization rate provides further evidence for the notion that both the individual experience of victimization and its overall rate in a classroom are associated with negative outcomes (Reuland & Mikami, ).…”
Section: Discussionmentioning
confidence: 97%
“…Our finding that girls reported more fear of victimization complies with the previously documented gender difference (Boulton et al ., ). The main effect of peer support complements the understanding of peer support as a feature relevant to various facets of adjustment (Galand & Hospel, ; Prinstein et al ., ). The main effect of classroom victimization rate provides further evidence for the notion that both the individual experience of victimization and its overall rate in a classroom are associated with negative outcomes (Reuland & Mikami, ).…”
Section: Discussionmentioning
confidence: 97%
“…Finally, conflicting results were reported with respect to maladjustment as mediator between peer victimization and school affection/connectedness-whereas Galand and Hospel (2013) showed that depression in combination with self-efficacy mediated this link, no support for associations between internalizing or externalizing problems and school connectedness was found by Loukas et al (2012).…”
Section: Mediators On Associations Between Peer Victimization and Schmentioning
confidence: 98%
“…Moreover, Kowalski and Limber (2013) found than among early and late American adolescents (Grades 6 to 12), the subgroup of youths who were both victims and bullies presented the poorest academic performance. Galand and Hospel (2013) showed that peer victimization was negatively associated with academic self-efficacy (viewed as a proximal predictor of achievement) in a sample of early adolescents in the French region of Belgium (Grades 7 and 8).…”
Section: Students' Perception Of Parental Supportmentioning
confidence: 99%